1981
DOI: 10.1185/03007998109114275
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin D metabolites in the osteomalacia of renal disease

Abstract: Osteomalacia is commonly found in patients with severe renal impairment. Its aetiology is multifactional and not simply due to deficient production of active metabolites of vitamin D. Decreased availability of calcium and phosphate and the accumulation of aluminium is some dialysis-treated patients are also important aetiological factors. The treatment of osteomalacia depends, in part, upon its accurate diagnosis, and identifying and reversing the underlying cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Clinical management of renal osteodystrophy includes the use of phosphate binders (aluminum hydroxide, calcium carbonate) to control phosphate intake, helping to maintain normal serum phosphate concentrations, and then treatment with 1,25(OH),D, (0.25-2.0 [i,g/d) (263). Some authors have suggested that a combined treatment with both 25(OH)D, (0.5-0.75 fxg/d) and 1,25(OH),D, (0.5-2.0 |ig/ d) is more efficacious than treatment with 1,25(OH),D, alone (264).…”
Section: Renal Osteodystrophymentioning
confidence: 99%
“…Clinical management of renal osteodystrophy includes the use of phosphate binders (aluminum hydroxide, calcium carbonate) to control phosphate intake, helping to maintain normal serum phosphate concentrations, and then treatment with 1,25(OH),D, (0.25-2.0 [i,g/d) (263). Some authors have suggested that a combined treatment with both 25(OH)D, (0.5-0.75 fxg/d) and 1,25(OH),D, (0.5-2.0 |ig/ d) is more efficacious than treatment with 1,25(OH),D, alone (264).…”
Section: Renal Osteodystrophymentioning
confidence: 99%
“…Osteomalacia is commonly found in patients with severe renal impairment, and its aetiology is multifactorial (Stanbury and Mawer, 1978b;Kanis et al, 1981). The kidney is the major site of production of the active metabolite 1,25(OH)2D.…”
Section: Causes Of Vitamin D Deficiencymentioning
confidence: 99%
“…Such patients commonly suffer from generalized bone disease including osteomalacia. Although the aetiology of this renal osteodystrophy is multifactorial, attention in recent years has centred on the role of disturbed vitamin D metabolism (Kanis et al, 1981). Numerous reasons have been suggested for the perceptive deafness associated with chronic renal failure, including osmotic disturbances during haemodialysis, potentiation of ototoxic drugs, premature arteriosclerosis, electrolyte imbalance and inadequate dialysis (Bergstrom et al, 1980;Kligerman et al, 1981).…”
Section: Clinical Casesmentioning
confidence: 99%